- PENGAMANAN ZONA EKONOMI EKSKLUSIF INDONESIA OLEH BADAN KEAMANAN LAUT: - - Muhammad Michael Kahfi; Anto Ismu Budianto (Reformasi Hukum Trisakti, 2023)
The implementation of law enforcement in Indonesian waters is carried out to maintain Indonesia's territorial integrity as well as safeguard and protect Indonesia's national interests at sea. The authority of the BAKAMLA agency over the Indonesian Exclusive Economic Zone (ZEEI), among other things, is carried out through arrests of foreign fishing vessels. The problem formulation in this article is how to implement BAKAMLA's authority in the Indonesian EEZ. Then, the type of research used in writing this article is normative law, descriptive in nature, the data used is secondary data and primary data analyzed qualitatively, and the method of drawing conclusions uses deductive logic. The results of the research and discussion are related to the BAKAMLA EEZ carrying out security and safety patrols in Indonesian waters and Indonesian jurisdictional areas. The authority in BAKAMLA is carried out in synergy between related agencies in an integrated manner, integrated into one unit of command. The conclusion of this research is that the implementation of BAKAMLA's authority is realized through hot pursuit, stopping, inspecting, arresting, taking and handing over the ship to the relevant authorized agency for further legal proceedings